Peace Education as the Development of Social Skill in Social Science Learning - Sariyatun Sariyatun; Hermanu Joebagio; Muhammad Akhyar (Paramita: Historical Studies Journal, 2019)
This research aims to describe the integration of peace education as the reinforcement of social skill reinforcement in Social Science learning. Qualitative research method was employed in this study. Data source included teachers, documents, and library study. Data collection was carried out using interview, questionnaire, and document and literature source analysis. Interview and questionnaire were used to explore the respondents’ perspective on peace education for developing social skill in Social Science learning. The subjects agreeing to participate in this study were Social Science teachers in Junior High School consisting of 20 teachers. The participants were selected using purposive sampling. Data validation was conducted using method triangulation and data analysis using an interactive model of analysis encompassing data reduction, data display, and data verification. From the result of research, it could be concluded that Social Science teachers in Surakarta had positive perception that peace education in Social Science learning can be used to reinforce social skill.